Manpower Planning - Hutapea, Aris (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
In term of human resource management, there are two dillematic problemscoming together. In one hand, in line with the progress of organization the more developing and complicated tasks and responsibilitiesof human resource, and the increasing demands on quality and quantit, cause the additional workload. On the other hand, the decreasing skills, knowledge, and motivation, which can be caused by the weakening memory, work boredom, age and other biological factors, may cause the decreasing work capacity. Undoubtedly, these two factors create a gap. Therefore, manpower planning should be carried out, covering with such strategies as empowerig thecompetent workforce , giving them opportunities to choose the appropriate jobs, helping them to optimize their energy, building self-confidence, sending them to education and training programs, stimulating their work imagination, awakening their work creativity and innovation, and implementing proper rotation and promotion.